Erratum: The Aggregate Implications of Regional Business Cycles. - Beraja, Martin; Hurst, Erik; Ospina, Juan (Econometrica, 2025)
The article addresses an error in the code used to generate results in a previously published paper on state-level wage measures during the Great Recession. The authors acknowledge the mistake of dividing total wages by the total number of individuals rather than the number of working individuals, which led to incorrect wage estimates. The erratum details the corrections made to the code, updates the relevant tables and figures, and presents revised estimates for the New Keynesian Wage Phillips Curve, indicating that while the magnitudes of the estimates have changed, the qualitative results remain consistent. The article emphasizes the importance of incorporating regional data in understanding aggregate business cycles.